1972
DOI: 10.1128/aem.24.4.540-543.1972
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte Flocculation as an Aid to Recovery of Enteroviruses from Oysters

Abstract: A simple and rapid method for recovering enteroviruses from oysters is described. A polycation sewage flocculant promoted cohesion of oyster solids and thereby aided separation of these from the viruses. Recovery of 80 to 100% of experimentally inoculated virus was achieved, and the suspension or extract obtained could be inoculated directly into tissue cultures or concentrated first for greater sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Organic flocculation in combination with the use of the polyelectrolyte Cat-Floc was considered responsible for the virtually noncytotoxic samples prepared by the improved method. Cat-Floc has been used previously for clarification of shellfish homogenates and as an aid in the separation of enteric viruses (11). The degree of sample clarification obtained was considered an important factor in the virtual elimination of cytotoxicity from samples of each of the three shellfish species studied.…”
Section: Discussionmentioning
confidence: 99%
“…Organic flocculation in combination with the use of the polyelectrolyte Cat-Floc was considered responsible for the virtually noncytotoxic samples prepared by the improved method. Cat-Floc has been used previously for clarification of shellfish homogenates and as an aid in the separation of enteric viruses (11). The degree of sample clarification obtained was considered an important factor in the virtual elimination of cytotoxicity from samples of each of the three shellfish species studied.…”
Section: Discussionmentioning
confidence: 99%
“…Microbiol. 1981, Q51, p. 209), cationic flocculant treatment (11), and filtration through positively charged filters (10). We found that freon treatment and positively charged filters were inadequate for removing cytotoxicity from crab concentrates.…”
Section: Discussionmentioning
confidence: 85%
“…ND, Not done. No 77 (69-100) 80 (69-100) 14 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) a Oyster samples (40 to 100 g) were inoculated with 20 to 2,000 PFU of virus, diluted 1:1 with water, and adjusted to pH 8.9. Catfloc was added if indicated, and the samples were centrifuged.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to 1978, ultrafiltration or ultracentrifugation was used for concentration of virus from shellfish samples (11,12). To determine the suitability for recovery of rotavirus and poliovirus from Canadian Atlantic oysters, several of these methods were compared by using oysters inoculated in the laboratory.…”
mentioning
confidence: 99%